Análise da regulação transcricional da rota metabólica de antocianinas e de seus transportadores em diferentes tecidos do fruto de tomateiro - Santos, Adolfo Luís dos (2017)
Anthocyanins are composed of the secondary metabolism of plants and are inserted into the flavonoid group. Anthocyanins are responsible for the purple pigmentation of fruits and present important functions not only for plants but also for human health. Thus, the enrichment of anthocyanins in fruits becomes important, being the tomato an ideal candidate for this enrichment as it is among the most consumed vegetables in the world. In addition to genetic engineering, classical breeding of plants through genotype crosses is a viable technique for achieving such enrichment. However, it is necessary to be aware not only of the route of anthocyanin biosynthesis in tomatoes, but also of the genes that regulate this route, such as transporters of that pigment in the cell. Currently known that in dicotyledons the initial phase of the anthocyanin route is regulated by R2R3-MYB transcription factors, whereas the late phase is regulated by the MYB-bHlH-WD40 (MBW) complex, in addition, MATE (Multidrug and Toxic Compound Extrusion) or ABC (ATP-Binding Cassette), are responsible for the transport of anthocyanin in the vacuole. Recently, a triple tomato mutant involving the Aft, atv and hp2 loci was generated. The genotype shows accumulation of anthocyanin, which gives purple coloration to the epicarp of the fruits. Recent works have identified two transcription factors (SlMYB114 and SlTT8), which are probably responsible for regulating anthocyanin biosynthesis in the Aft / atv / hp2 genotype. In this work we studied the accumulation of anthocyanin in edible fleshy foods, we report characteristics of the development of Aft / atv / hp2 genotype plants, characterize the MATE family of proteins in Solanum lycopersicum and point out a probable MATE protein responsible for transporting anthocyanin in tomatoes, In addition, we constructed binary vectors for future tomato plant transformations in order to prove the functions of genes previously identified by concomitant superexpression of the SlTT8 and SlMYB114 factors in wild red fruit tomatoes, as well as the suppression of the specific gene expression of SlMYB114 in fruits Purples via CRISPR / Cas9. This work brings previously unknown data on the recent Aft/atv/hp2 genotype and on MATE proteins in Solanum lycopersicum that will serve as the basis for new research on the transport not only of anthocyanins but of several other important compounds for the metabolism and development of both the Tomato, as of other Solanaceae.